The Effectiveness of Visual Number Card Media in Enhancing the Counting Skills of Students with Mild Intellectual Disabilities - Maimanah, Asnahul; Nugraha, Enung; Rachmiati, Wida (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aimed to examine the extent to which the use of pictured number card media influences the counting ability of students with mild intellectual disabilities at the Special School (Sekolah Khusus/Fauzan SKh) in Serang Regency. the primary research question was whether the use of pictured number card media had a significant effect on the counting skills of students with mild intellectual disabilities at Fauzan Special School. The hypotheses of this study comprised a null hypothesis (Ho), which stated that the media had no effect on the students’ counting skills, and an alternative hypothesis (H1), which posited a significant effect. The study employed a pre-experimental method using a one-group pretest-posttest design. The population consisted of 23 students with special needs, from which a sample of 10 students with mild intellectual disabilities was selected. Data were collected through tests, observations, and documentation. The results, analyzed using the Wilcoxon Matched Pairs test at a significance level of 0.05, yielded ap-value of 0.005. Since this value was less than 0.05, the null hypothesis (Ho) was rejected. These findings indicated that the use of pictured number card media significantly improved the counting skills of students with mild intellectual disabilities.